Stages in the development of the legislation of the Republic of Kazakhstan in the field of insurance activity (Journal of actual problems of jurisprudence, 2018)
In this article, the author describes the main stages of development of insurance legislation in the Republic of Kazakhstan. It was stated that in ancient Rome laid the foundation of the insurance mechanism. Formation of the insurance legislation in the territory of present-day Kazakhstan has its origins in the Soviet period. Together with the stages of development of domestic insurance, described some features of the development of insurance activities in foreign countries. We used the works of local authors as Mynbaeva NB, and the authors of the Russian Federation and the Far East.Key words: insurance activities, marine insurance, the establishment of insurance legislation.